Reward Systems and Employee Performance in the Print Media Sector In Kenya - Rugami, Irene; Wambua, Dr. Philip; Mwatha, Dr. Stephen (European Journal of Business and Strategic Management, 2016)
Purpose: The purpose of this study was to establish the influence of reward systems on employee performance in the media industry in Kenya. Methodology: The study used an explanatory research design. The population of this study was the employees of 4 daily newspapers namely daily nation, standard, people daily and the star. The total number of employees was 980 broken down into 26 managers, 104 supervisors and 850 other staff. The sample size was 105.Data was collected by use of questionnaires. The questionnaires consisted of structured closed ended statements. Data was analyzed mainly by use of descriptive and inferential statistics. Descriptive statistics included mode, mean, median, standard deviation. Inferential statistical techniques like correlation and regression coefficients were used to draw causal relationship between the various reward system and performance. Data was presented by use of graphs, pie charts and tables. Results: The study findings indicate that extrinsic reward improved performance of employees, the intrinsic reward to a large extent is a contributory factor to employee performance, organization reward is crucially important and indispensable factor to employee performance while team based reward systems encouraged free riding and stifle individual performance. Unique contribution to theory, practice and policy: The study recommended that print media industry sector should get to know their employees well so that they can employ the right motivational strategy. In addition, the study recommends that in order to enhance employees' motivation and performance, print media sector should adopt a more contingent reward system which includes awards and fringe benefits to the employees. The management should come up with a clear cut reward system that ensures that all employees are rewarded appropriately.